The emerging role of Imatinib in malaria management: a review of evidence and future directions - Victor Oluwatomiwa Ajekiigbe; Chidera Stanley Anthony; Ikponmwosa Jude Ogieuhi; Jonathan Oluwafemi Adeola; Peace Uchechi Bassey; Pelumi Gbolagade-Jonathan; Stephen Olaide Aremu; Akintunde Abisoye Omoleke; Ifeoluwa Sandra Bakare; Adedoyin Veronica Babalola (Tropical Diseases, Travel Medicine and Vaccines)
Abstract Background Malaria still remains one of the leading causes of death, especially in Africa, with one of the major struggles associated with eradication being resistance to antimalarial medications. Imatinib, a selective tyrosine kinase inhibitor used to treat chronic myeloid leukemia, has emerged as a potential pharmacological approach for malaria management. Methods This review synthesizes studies from the inception of the databases of PubMed, Scopus, Google Scholar, Cochrane, Web of Science, and Embase to February 2025, identifying key clinical trials and invitro studies conducted to assess the efficacy and safety of Imatinib in malaria. Results With varying sample sizes, dosage and follow-up data, the studies reported a decline in parasite density, pyrexia, parasite growth inhibition, and synergism with other anti-malarial medications like Artesunate. Across the nine (9) studies reviewed, Imatinib showed a favorable safety profile with no adverse drug-related events reported. Conclusions We discuss the potential advantages and challenges of repurposing Imatinib for treating malaria, its pharmacokinetic profile, and its use in other patient populations, such as children and pregnant women. Future studies should focus on randomized controlled trials with larger sample sizes and possible combination therapies with other antimalarial medications.